The mediating role of emotional competence in the association between self-esteem and cyberbullying victimization among adolescents - Mauludi, Muhammad Irsyad; Fasikhah, Siti Suminarti (Jurnal Ilmiah Psikologi Terapan, 2024)
The transition phase experienced by adolescents is certainly not always smooth and it is common to experience bullying. With the development of technology, bullying that was originally only in schools and neighborhoods has become in cyberspace or can be called cyberbullying. someone can become a victim of cyberbullying because they have low self-esteem. Emotional competence, which includes the ability to recognize, respond, and manage one's own and others' emotions, is a key factor in overcoming the negative impact of cyberbullying and improving adolescents' self-esteem. This study aims to examine the important role of emotional competence as a mediator between self-esteem and cyberbullying victimization in adolescents. In this study, a sample of 115 adolescents who had experienced cyberbullying was involved. A significant indirect effect (-0.1022) of emotional competence was found through data analysis using mediation tests. The findings of this study provide strong evidence that adolescents with high self-esteem and good emotional competence are likely to experience lower impact when victimized by cyberbullying. The results of this study provide a deeper understanding of the importance of developing emotional competence in protecting adolescents from the risks and negative impacts of cyberbullying. Emotional competence can be learned by attending some training such as emotion regulation training, emotion identification, and others that are related to emotional competence. Self-esteem training also can be an option for adolescents to learn and increase the skill of emotional competence.